MAIN ASPECTS OF ORGANIZING STUDENT HEALTH ACTIVITIES: MAIN ASPECTS OF ORGANIZING STUDENT HEALTH ACTIVITIES - to'ychiyev, sobir (Физическое воспитание, спорт и здоровье, 2022)
This research paper provides theoretical information and practical recommendations on the impact of health interventions on the health and physical fitness of primary school students.